PERAN KEGIATAN KOKURIKULER ADIWIYATA BERBASIS PROJEK DALAM MEMBENTUK KARAKTER PEDULI LINGKUNGAN SISWA SEKOLAH DASAR - Rusmiati, Esih; Handayani, Sri; Wasliman, Eva Dianawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Project-based Adiwiyata co-curricular activities are a series of out-of-class learning activities designed systematically and integrated with the Adiwiyata Program to foster environmental care character in elementary school students. Effective implementation requires management that encompasses planning, organizing, implementing, and monitoring. This study aims to describe and analyze the role of project-based Adiwiyata co-curricular activities in shaping students' environmental care character from the perspective of educational management. This research employed a qualitative approach with a case study method. Data collection techniques included interviews, observation, documentation studies, and data triangulation. The study was conducted at SDN 099 Babakan Tarogong, involving the principal, teachers, students, the Adiwiyata coordinator, and parents as research subjects. The results indicate that the planning of project-based Adiwiyata co-curricular activities is systematically structured based on the school’s vision and mission. The organization of activities is supported by a clear organizational structure and proportional task distribution. The implementation is carried out actively and participatively through cleanliness activities, waste reduction, waste segregation, waste processing, plant maintenance, and school garden management. Inorganic waste is processed into handicrafts and ecobricks, while organic waste is processed into compost, MOL (local microorganisms), and eco-enzymes. Activity evaluation is conducted continuously by assessing both the process and the outcomes. Overall, project-based Adiwiyata co-curricular activities play a significant role in fostering environmental care character, as reflected in consistent changes in students' attitudes, behaviors, and environmental habits